A robust zirconium amino acid metal-organic framework for proton conduction. Issue 1 (December 2018) - Wang, Sujing; Wahiduzzaman, Mohammad; Davis, Louisa; Tissot, Antoine; Shepard, William; Marrot, Jérôme; Martineau-Corcos, Charlotte; Hamdane, Djemel; Maurin, Guillaume; Devautour-Vinot, Sabine; Serre, Christian
Abstract Proton conductive materials are of significant importance and highly desired for clean energy-related applications. Discovery of practical metal-organic frameworks (MOFs) with high proton conduction remains a challenge due to the use of toxic chemicals, inconvenient ligand preparation and complication of production at scale for the state-of-the-art candidates. Herein, we report a zirconium-MOF, MIP-202(Zr), constructed from natural α-amino acid showing a high and steady proton conductivity of 0.011 S cm−1 at 363 K and under 95% relative humidity. This MOF features a cost-effective, green and scalable preparation with a very high space-time yield above 7000 kg m−3 day−1 . It exhibits a good chemical stability under various conditions, including solutions of wide pH range and boiling water. Finally, a comprehensive molecular simulation was carried out to shed light on the proton conduction mechanism. All together these features make MIP-202(Zr) one of the most promising candidates to approach the commercial benchmark Nafion. Metal-organic frameworks are promising materials for proton exchange membrane fuel cells, but cumbersome ligand preparation and use of toxic metals or solvents hinders their application. Here, the authors report the green synthesis of a zirconium, amino acid-based MOF that displays high proton conductivity and excellent stability.